Effects of Yoga on Blood Glucose and Lipid Profile of Type 2 Diabetes Patients Without Complications: A Systematic Review and Meta-Analysis - Chen, Shanshan; Deng, Shilin; Liu, Yang; Yin, Tiantian (Frontiers in Sports and Active Living, 2022)
Purpose: The purpose of this study is to examine the effect of yoga training on diabetes-related indicators compared with usual care. Methods: The review protocol of this study has been registered in the PROSPERO with a registration number CRD42021267868. A systematic literature search through electronic databases was conducted to identify yoga-based intervention (i.e., randomized controlled trial [RCT]; e.g., yogic postures, movements, breathing, and meditation) studies reporting outcomes on glycosylated hemoglobin (HbA1c), fasting blood glucose (FBG), post-prandial blood glucose (PPBG), total cholesterol (TC), triglycerides (TG), and body mass index (BMI). Two researchers manually reviewed and assessed each article using the Cochrane Risk of Bias Tool 2.0. The literature search identified 296 eligible entries, of which 13 were finalized after screening using predefined inclusion and exclusion criteria. The extracted data (group mean and standard deviation at posttest) were synthesized using random-effects meta-analyses. Finally, potential moderators were explored using subgroup analysis and sensitivity analysis. Results: Standardized mean difference for the effects of yoga were significant on HbA1c (MD = -0.47; 95%CI: -0.77, -0.16; Z = 3.02, P = 0.003), FBG (SMD = -0.92; 95%CI: -1.55, -0.29; Z = 2.87, P = 0.004), PPBG (SMD = -0.53; 95%CI: -0.86, -0.21; Z = 3.20, P = 0.001), and TG (SMD = -0.32; 95%CI: -0.54, -0.10; Z = 2.86, P = 0.004). However, yoga effect was not observed on TC (SMD = -0.84; 95%CI: -1.71, 0.04; Z = 1.87, P = 0.06) and BMI (MD = -0.63; 95%CI: -1.42, 0.16; Z = 1.57, P = 0.12). Conclusion: The findings suggest that yoga can improves the biochemical indices of blood glucose and the lipid profile of T2DM patients. Therefore, yoga can be prescribed as an effective and active complementary treatment for T2DM. However, this study only tested yoga as a short-term treatment. In the future, rigorous RCTs with a larger sample size may be carried out to examine the long-term effect of yoga on T2DM.